Canadian journal of kidney health and disease (BioMed Central, 2014)
"Canadian Journal of Kidney Health and Disease, the official journal of the Canadian Society of Nephrology, is an open access, peer reviewed online journal that promotes the highest quality publications focused on clinical, translational and health services delivery research in the field of chronic kidney disease, dialysis, kidney transplantation and organ donation."